Current Trends in Food-Derived Peptidic Antioxidants - Henry M. Corpuz; Soichiro Nakamura; Shigeru Katayama (MDPI AG, 2022)
Recently, peptidic antioxidants have attracted much attention due to their promising applications in the production of valuable functional food and nutraceuticals with health-promoting properties [...]